TRANSFORMASI KONSEP ENTREPRENEURSHIP DALAM PENDIDIKAN DI ERA DIGITAL - Rosmiati, Rosmiati; Trisnawati, Winda; Aryanti, Puji Tri; Anwar, Anwar (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research aims to determine the transformation of the concept of entrepreneurship from time to time. This research is a literature study in which the collection of information is obtained from books, scientific articles that are relevant to the topic of this research. The results of this study reveal the concept of Entrepreneurship which has been transformed from prehistoric times to this digital era. The concept of entrepreneurship, which in prehistoric times was in the form of bartering, is currently changing into technopreneurship. Technopreneurship must succeed in two main tasks, namely: ensuring that the technology functions according to the needs of target customers, and that the technology can be sold at a profit. Technopreneur then creates a new business model called startup. The future of technopreneurs related to startups that might happen is the emergence of technopreneurs who develop future startups.